Transcriptomic Analysis of Wheat Under Multi LED Light Conditions - Lei Sun; Ding Li; Chunhong Ma; Bo Jiao; Jiao Wang; Pu Zhao; Fushuang Dong; Shuo Zhou (Plants)
Light is a vital environmental cue that profoundly influences the development of plants. LED lighting offers significant advantages in controlled growth environments over fluorescent lighting. Under monochromatic blue LED light, wheat plants exhibited reduced stature, accelerated spike development, and a shortened flowering period with increased blue light intensity promoting an earlier heading date. In this study, we conducted a comprehensive transcriptome analysis to investigate the molecular mechanisms underlying wheat plants’ response to varying light conditions. We identified 34 types of transcription factors (TFs) and highlighted the dynamic changes of key families such as WRKY, AP2/ERF, MYB, bHLH, and NAC, which play crucial roles in light-induced gene regulation. Additionally, this study revealed differential effects of blue and red light on the expression levels of genes related to hormones such as cytokinin (CK) and salicylic acid (SA) synthesis as well as significant changes in pathways such as flavonoid biosynthesis, circadian rhythms, chlorophyll synthesis, and flowering. Particularly, blue light upregulated genes involved in chlorophyll synthesis, contrasting with the downregulation observed under red light. Furthermore, blue light enhanced the expression of anthocyanin synthesis-related genes, such as CHS, underscoring its role in promoting anthocyanin accumulation. These findings provide valuable insights into how light quality impacts crop growth and development.